Pengaruh Motivasi Belanja Hedonis dan Fashion Involvement Terhadap Pembelian Impulsif Secara Online Dikota Makassar - HR, Musdalifah; Baharuddin, Dahliah; Saleh, Anies (STIE AMKOP, 2024)
The research aims to: 1). To find out and analyze the influence of hedonic shopping motivation on online impulsive purchases in the city of Makassar. 2). To find out and analyze the influence of fashion involvement on online impulse buying in the city of Makassar. 3). To determine the influence of hedonic shopping motivation and fashion involvement simultaneously on online impulsive purchases in Makassar City. This research is quantitative research. The sampling technique used accidental sampling technique, and the number of samples used was 100 respondents. The data collection technique is primary data or data taken directly from respondents via questionnaires. The analysis technique uses multiple linear regression. The independent variable in this research is impulse buying while the dependent variable is hedonic shopping motives and fashion involvement. This research obtained the results that: 1). Hedonic shopping motivation has a positive and significant effect on online impulse purchases in Makassar City. 2). fashion involvement has a positive and significant effect on online impulse buying in the city of Makassar. 3). Hedonic shopping motivation and fashion involvement simultaneously have a positive and significant effect on online impulse buying in the city of Makassar. Keywords: Hedonic shopping motivation, fashion involvement and impulse buying.